Complementarity versus substitutability of dynamic and operational capabilities in B2B firms: A configurational approach - Nagy, Gábor; Jaakkola, Matti; Koporcic, Nikolina (Industrial marketing management, 2019)
Despite extensive research into dynamic and operational capabilities, understanding of their interplay is still scant. Both complementary and substitutive roles have been proposed in prior conceptual studies, but only limited systematic empirical investigations into the mutual interdependence of these capabilities have been conducted. Drawing on a sample of 219 Hungarian B2B firms, this study incorporates prior literature on dynamic and operational capabilities and employs a set-theoretical approach to examine whether the capabilities complement or substitute each other in producing high levels of business performance. While evidence for both types of interdependency is provided, the findings generally support the view that dynamic and operational capabilities are complementary rather than substitutive. The two types of capabilities also explain business performance better jointly than in isolation. Several effective capability configurations, associated with high business performance, are identified. The findings paint a detailed picture of the complex interplay between dynamic and operational capabilities, thereby contributing to academic and managerial audiences alike. •The results support to the view that customer focus and product orientation are two distinct objectives that appear difficult to reconcile. However, configuration analyses show that some firms may still be able to manage customer-centric product development if other capabilities are in place, and if such capability configurations match internal and external organizational contingencies.•The hierarchical interrelatedness of dynamic capabilities and their stimulating effect on operational capabilities and business performance appears to have empirical support but remains relatively scarce across configurations and different types of performance outcomes.•Dynamic capabilities can themselves contribute to high financial performance.•Moreover, the configurations imply that most of the operational and dynamic capabilities co-occur with a high level of competitive intensity and, in some cases (though with less frequency), with a high level of technological turbulence.•In addition, the results indicate that small firms may not be able to manage a wide range of capabilities and are more likely to developing their core activities (/competencies) and specializing in specific skills.